Challenges of financial inclusion policies in Peru - Boitano Castro, Guillermo Rafael (2020)
The purpose of the research is to identify the main determinants of financial inclusion in Peru at the department level (without Lima) from 2010 to 2017, aiming to analyze the challenges faced by financial inclusion policies. A two-stage GMM method was used to estimate a panel data model where the endogenous variable is Sarma’s financial inclusion index (2008). The results indicate that bank concentration is the main variable affecting financial inclusion. At the same time, although the effect of technology is positive, it is diminishing over time due to the inefficient deployment of such technology and, in many cases, a lack of knowledge on how to use it, especially in the remote areas of Peru.